Provably good and practically efficient algorithms for CMP - Chunyang Feng; Hai Zhou; Changhao Yan; Jun Tao; Xuan Zeng (2009 46th ACM/IEEE Design Automation Conference, 2009)
To reduce chip-scale topography variation in chemical mechanical polishing (CMP) process, dummy fill is widely used to improve the layout density uniformity. Previous researches formulated the dummy fill problem as a standard linear program (LP). However, solving the huge linear program formed by real-life designs is very expensive and has become the hurdle in deploying the technology. Even though there exist efficient heuristics, their performance cannot be guaranteed. In this paper, we develop a dummy fill algorithm that is both efficient and with provably good performance. It is based on a fully polynomial time approximation scheme [Fleischer, 2004 ] for covering LP problems. Furthermore, based on the approximation algorithm, we also propose a new greedy iterative algorithm to achieve high quality solutions more efficiently than previous Monte-Carlo based heuristic methods. Experimental results demonstrate the effectiveness and efficiency of our algorithms.